2013
DOI: 10.1007/s00431-013-2066-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing breastfeeding duration: a survey in a Turkish population

Abstract: Our findings suggest several strategies to increase the duration of breastfeeding, including educating fathers along with mothers, supporting a shared bedroom until the child is 2 years of age, and promoting measures that allow mothers to be with their children during working hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
1
19
0
4
Order By: Relevance
“…It is a source of protein, lipid, oligosaccharide, vitamins, elements, hormones, enzymes, growth and immune factors that can adjust over time based on infant's need [1]. Breastfeeding protects children against respiratory tract infections, atopic dermatitis, asthma, type II diabetes, obesity, and sudden infant death syndrome [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is a source of protein, lipid, oligosaccharide, vitamins, elements, hormones, enzymes, growth and immune factors that can adjust over time based on infant's need [1]. Breastfeeding protects children against respiratory tract infections, atopic dermatitis, asthma, type II diabetes, obesity, and sudden infant death syndrome [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some observational studies dealing with maternal factors affecting initiation and continuation of breast feeding revealed that mother's age, education or parity did not affect the rate of breast feeding (10), while others noticed that older age, higher maternal education and multi-parity were associated with higher likelihood of breast feeding at 6 months of age (6)(7)(8). On the other hand, maternal employment, cesarean delivery and infant hospitalization are recognized risk factors for early discontinuation of EBF (10,14,15,25).…”
Section: Resultsmentioning
confidence: 99%
“…Hospital practices and training of health care personnel in accordance with the Baby friendly hospital initiative (BHFI), is another important variable that may have an enormous impact on the rate of EBF (39)(40)(41)(42)(43)(44). Several of these factors may be interdependent, for example, delivery of low birth weight may result in neonatal hospitalization, mother-baby separation, and nonobservance to recommendations of BHFI (1,10,17,24,25,(39)(40)(41)(42)(43)(44). Apart from health care settings, another potential confounder affecting infant feeding patterns in a community are the food-marketing strategies practiced by the multi-national baby formula companies, (the socalled infant food industry), and the degree of control exercised by government legislation on inappropriate formula advertising by these trade giants (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo realizado com mães escocesas identificou o emprego e o retorno precoce ao trabalho são fatores associados à menor duração do AM (SKAFIDA, 2012). Outra pesquisa obteve índices menores de duração do tempo de AM em mulheres que trabalhavam fora do que em mães donas de casa na Turquia, sendo, respectivamente, 13,3±5,7 meses e 15,8±6,0 meses (SENCAN; TEKI; TATLI, 2013). No Brasil, intervenções no ambiente laboral no intuito de estimular o AM não parecem ser uma prática adotada por empregadores e empresas, salvo as pausas no trabalho, garantidas mediante legislação específica.…”
Section: Fatores Que Se Relacionam Ao Desmame Precoce: Implicações Maunclassified